Інтенсивність зношування породоруйнівних елементів з КАМ залежно від хімічного складу та способу нанесення покриттів на алмазні зерна - Майстренко, А.Л.; Закора, А.П.; Шмегера, Р.С.; Супрун, М.В.; Виноградова, О.П.; Бєляєв, А.С.; Петасюк, Г.А.; Ростоцький, І.Ю.; Панова, А.М.; Заболотний, С.Д. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2017)
Досліджено інтенсивність зношування робочої поверхні породоруйнівних елементів з композиційних алмазовмісних матеріалів (КАМ) при руйнуванні пісковику Торезького родовища. Як зразки використано КАМ на основі матриці NiSn (6%) з алмазами марки АС 300Т зернистістю 400/315 мкм без покриття та з покриттями гідридом титану та хрому, нанесеними механічним способом; на основі матриці NiSn (6%) з алмазами марки АС160Т зернистістю 400/315 мкм з покриттям корбідом титану TiC, нанесеним іонно-плазмовим способом, а також матеріал «Славутич» на зв’язці WC+Co з природними алмазами зернистістю 600/530 мкм. У результаті експериментальних досліджень інтенсивності зношування зразків з КАМ та мікроскопічного дослідження їх робочої поверхні зроблено висновок про найнижчу інтенсивність зношування зразка зі «Славутича» та елемента з механічно вкритими Сr алмазами. Исследована интенсивность изнашивания рабочей поверхности породоразрушающих элементов из композиционных алмазосодержащих материалов (КАМ) при разрушении песчаника Торезского месторождения. В качестве образцов использованы КАМ на основе матрицы NiSn (6%) с алмазами марки АС 300Т зернистостью 400/315 мкм без покрытия и с покрытием гидридом титана и хрома, нанесенными механическим способом; на основе матрицы NiSn (6%) с алмазами марки АС160Т зернистостью 400/315 мкм с покрытием корбидом титана TiC, нанесенным ионно- плазменным способом, а также материал «Славутич» на связке WC+Co (6%) с природными алмазами зернистостью 600/530 мкм. В результате экспериментальных исследований интенсивности изнашивания образцов из КАМ и микроскопического исследования их рабочей поверхности пришли к выводу о наиболее низкой интенсивности изнашивания образца из «Славутича» и элемента с механически покрытыми Сr алмазами. In the paper, the intensity of wearing of the working surface of the rock-breaking elements from composite diamond- containing materials (CDM) with different chemical composition of the matrix material during the destruction of the sandstone of the Torez deposit was studied on a special stand, created on the basis of a lathe screw machine, model DIP-200.The following CDM were used as the samples: based on a NiSn (6%) matrix with DS 300T diamonds with a grain size of 400/315 mm, uncoated and coated titanium hydride and chromium, which were applied mechanically; based on the NiSn (6%) matrix with diamonds of the grade DS 160T with a grain size of 400/315 mm with Titanium carbide coating by ion-plasma method, as well as the material "Slavutich" on the WC + Co (6%) with natural diamond with a grain size of 600/530 mm. As a result of the carried out experimental studies of the intensity of wear of samples from CDM, microscopic study of their working surface of the rock-breaking elements (protrusion above the matrix surface of the diamond grains, the number of holes from spent diamonds) and microscopic studies of geometric parameters of sludge particles, it was concluded that the wear rate of the sample from Slavutich and the element with mechanically coated Cr diamonds is the lowest. In addition, all the elements from the CDM on a NiSn (6%) bond, whose diamonds have been coated, show thermal conductivities 11–18% higher, than a similar uncoated samples. This indicates the likely formation of a carbide phase at the diamond / bond interface during sintering, which improves contact between the diamond and the binder.